Integrasi Budaya Lokal Dalam Iklan Sebagai Strategi Pemasaran Produk Global - Shambodo, Yoedo; Ibrahim, Fachmi; Ismah, Syadiyah Nur; Katigo, Zahrio Herlanda (Universitas Al Azhar Indonesia, 2025)
Cultural integration is an important approach in an increasingly connected global environment, enabling organizations to respect and utilize cultural diversity to achieve their goals more effectively. This research highlights the importance of understanding and utilizing local cultural elements in global brand marketing campaigns to increase product appeal in local markets through advertising activities designed by advertising agencies. Advertising agencies have a key role in this process, as they are responsible for creating advertising content that is culturally sensitive and relevant to target audiences in different parts of the world. One of the global companies or brands that is trying to integrate culture in its advertising is Lalamove through the global campaign